Smart System Augmented Reality For Cultural and Tourism Mapping in North Padang Lawas - Rosyid, Januard; Rahayu Putri, Perra Budiarti; Irawan, Feri; Harahap, Hartati (P3M Politeknik Negeri Bengkalis, 2024)
The era of digital technology continues to develop rapidly which opens up new opportunities, including in cultural mapping and tourism. The aim of this research is to develop and evaluate the effectiveness of the Augmented Reality AR system in improving tourism experiences and cultural understanding in North Padang Lawas with innovations in improving tourism experiences through AR. The cultural and tourism potential of North Padang Lawas includes Bahal I Temple, Bahal II Temple, Bahal III Temple, Aek Milas Pangirkiran, Sagayung Lake, Danao Tao, Paya Goti Lake and Siombob Waterfall. The use of AR in cultural and tourism mapping makes it easier for tourists to navigate with additional information presented interactively. The research method stages are: First, Literature Study: collecting information about AR technology, Second, Survey and Interview: interviews with tourists, local communities, tourism stakeholders and cultural experts. Third Prototype Development: Developing an AR application prototype. Fourth Testing and Evaluation: Testing the AR application can run on an Android smartphone and the AR application can scan tourist and cultural barcodes. Next, evaluate the effectiveness of the application in improving tourism experiences and understanding of cultural heritage in North Padang Lawas. Fifth Data Analysis: data obtained from surveys, interviews and application testing to evaluate the success of applying AR technology in cultural and tourism mapping in North Padang Lawas. AR technology in tourism and culture can enrich tourism and culture with different interactive experiences, education, digitalization, tourism and culture preservation and innovation in developing mapping of cultural and tourist objects